ASPEK PERLINDUNGAN ANAK DALAM TINDAK KEKERASAN (BULLYING) TERHADAP SISWA KORBAN KEKERASAN DI SEKOLAH (Studi Kasus di SMK Kabupaten Banyumas) - Muhammad, Muhammad (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Children is nation future asset and router generation dream of nation, so children is entitled to the continuity of life, grow, and expand, participating and entitled of protection from discrimination and also have civil rights and freedom. These days there are aggressive behaviors and depress to the children, in the form of physical action and bullying that happened in education environment start from base level till college. From research result, physical bullying counted 9 times; verbal bullying counted 14 times and of bullying physical/ mental counted 8 times. This Bullying done by psychical and verbal. Bullying cause separate impact for student. Legal protection of student at school arranged in Law No.32 year 2002 concerning Protection of child. Kata Kunci: anak, bullying, perlindungan hukum